The effectiveness of the parent-child interaction intervention program based on emotion coaching on the symptoms of children\'s separation anxiety disorder - Masoomeh Takhti; AbdolAllah Shafi' Abadi; Atousa Kalantar Hormozi; Noor Ali Farrokhi (مجله علوم روانشناختی, 2021)
Background: Numerous studies have been conducted on the effectiveness of the parent-child interaction intervention program and the symptoms of separation anxiety disorder in children. However, research that has addressed the effectiveness of the parent-child interaction intervention program based on emotion coaching on symptoms of separation anxiety disorder has been overlooked. Aims: The aim of this study was to evaluate the effectiveness of the parent-child interaction intervention program based on emotion coaching on the symptoms of separation anxiety disorder in children. Method: Experimental research with pre-test-post-test design with Yood control group. The statistical population of the study included all female primary school girls in District 10(1282 person) in the academic year of 2019-2020. Thirty students were randomly selected for cluster sampling and randomly assigned to two experimental and control groups (15 subjects). The research tools are: Measurement of Separation Anxiety Scale (Parent-Child Version, Han, Hajinlian, Essen, Wender and Pinkas, 2003) and Parent-Child Interactive Intervention Program Based on Emotional Coaching (Researcher Made, 2019). Data analysis was performed using multivariate and single variable covariance analysis (MANCOVA). Results: The parent-child interaction intervention program based on emotion coaching was significantly effective in reducing the fear of liberation, fear of loneliness, fear of disease and worry about the occurrence of dangerous events (P< 0/01). Conclusions: Students who participated in the parent-child interaction intervention program based on emotion coaching had fewer symptoms of separation anxiety disorder.